The quest for nanoparticle-powered vaccines in cancer immunotherapy - Zhe Sun; Hui Zhao; Li Ma; Yanli Shi; Mei Ji; Xiaodong Sun; Dan Ma; Wei Zhou; Tao Huang; Dongsheng Zhang (Journal of Nanobiotechnology, 2024)
Abstract Despite recent advancements in cancer treatment, this disease still poses a serious threat to public health. Vaccines play an important role in preventing illness by preparing the body's adaptive and innate immune responses to combat diseases. As our understanding of malignancies and their connection to the immune system improves, there has been a growing interest in priming the immune system to fight malignancies more effectively and comprehensively. One promising approach involves utilizing nanoparticle systems for antigen delivery, which has been shown to potentiate immune responses as vaccines and/or adjuvants. In this review, we comprehensively summarized the immunological mechanisms of cancer vaccines while focusing specifically on the recent applications of various types of nanoparticles in the field of cancer immunotherapy. By exploring these recent breakthroughs, we hope to identify significant challenges and obstacles in making nanoparticle-based vaccines and adjuvants feasible for clinical application. This review serves to assess recent breakthroughs in nanoparticle-based cancer vaccinations and shed light on their prospects and potential barriers. By doing so, we aim to inspire future immunotherapies for cancer that harness the potential of nanotechnology to deliver more effective and targeted treatments. Graphical abstract